Effect of dietary supplementation ofliquid distillery stillage on growth per formance of Rajasri chicks (Indian Journal of Animal Production and Management, 2025)
The present study was conducted at institutional poultry farm of Krishi Vigyan  Kendra, Nandyal District, Andhra Pradesh, India to evaluate the effects of dietary  liquid distillery stillage (LDS) supplementation on the growth performance of the  Rajasri chicks. A total of 60 one-week-old Rajasri chicks were divided into three  groups, and each group supplemented a different dietary treatment: T0 (basal diet  without antibiotic), T1 (70% basal diet + 30% LDS), and T2 (50% basal diet + 50%  LDS).The results indicated significant differences in growth among the dietary  treatments. The highest average feed intake was observed in T2across all four weeks.  Similarly, T2 showed the highest average body weight gain, suggesting better growth  compared to T0 and T1. Moreover, T2 consistently exhibited the lowest FCR across  all four weeks, indicating better feed efficiency compared to the other treatments.  On the other hand, T1 showed intermediate performance in all three parameters,  while T0 had the least favourable outcomes. From the experiment, it was concluded  that, the supplementation of LDS in the diet of Rajasri chicks at 50% have resulted  in improved feed intake, body weight gain, and feed efficiency, indicating enhanced  growth performance. These findings underscore the significance of optimizing  feed formulations to support better growth and productivity in poultry production  systemsto achieve optimal growth and profitability in poultry farming.
Keywords: Rajasri chicks; Liquid Distillery Stillage; hicks, Liquid Distillery Stillage,; Feed intake and Feed Conversion Ratio